Incidence of Postoperative Pain After Single- and Multiple-Visit Root Canal Treatment in Patients Reporting in the Conservative Dentistry and Endodontics Outpatient Department of a Tertiary Care Hospital: A Cross-Sectional Study - Singla Munish; Kaur Harleen; Mittal Litik; Gupta Saloni; Kaur Savrose (Wolters Kluwer Medknow Publications, 2024)
This study aimed to conduct a human study to determine the incidence of postobturation pain using different parameters. In this cross-sectional study, 240 patients were included, which were equally allocated into two groups: single visit and multiple visit, 120 in each. Patients in both the single and multiple visits were further categorized into two subgroups, subgroup 1-no occlusal reduction and subgroup 2-occlusion reduction each having 60 patients. Corresponding to the type of visit, patients were followed by the role of medication into two groups, subgroup 1-both analgesics and antibiotics, subgroup 2-only analgesics, and subgroup 3-no medication. Following this approach and the criteria of the study, patients' performa was made, and based on this performa, the intensity of subjective symptoms, particularly postobturation pain, was determined using the visual analog scale (VAS). The data were then analyzed using the Chi-square test. Results were such that a single visit, no occlusal reduction, and only analgesics will be better for patients with irreversible pulpitis as chosen in the present study. Within the limitations of the present study, it can be concluded that single-sitting root canal treatment should be preferred over multiple sitting where there is no periapical inflammation; also, the occlusal reduction could be exempted from the same. To relieve the patient from postoperative pain where complete debridement is possible, antibiotics can be excluded from the regimen and only analgesics could be prescribed.